2007
DOI: 10.1097/01.ico.0000244873.08127.3c
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Central Corneal Thickness During the Menstrual Cycle in Women

Abstract: The central corneal thickness changes during the menstrual cycle; the cornea is thinnest at the beginning of the cycle and thickest at the end. These changes could be secondary to hormonal influences; estrogen receptors can be found in human corneas, suggesting that estrogen may have a role in corneal physiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 12 publications
2
75
1
3
Order By: Relevance
“…A similar magnitude of difference was observed by Kanellopolous and Asimellis [2]. Findings from previous investigations suggest that endocrine differences may affect ocular tissue growth [20,21]. Interestingly, variations in corneal thickness have been found in women during different phases of the Fig.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A similar magnitude of difference was observed by Kanellopolous and Asimellis [2]. Findings from previous investigations suggest that endocrine differences may affect ocular tissue growth [20,21]. Interestingly, variations in corneal thickness have been found in women during different phases of the Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Gray sectors Sectors where there was no significant correlation, white sectors sectors where there was a significant difference (partial correlation test, controlled for gender and spherical equivalent refraction). Significantly different at P \ 0.05, *P \ 0.01, and **P \ 0.001 Age-related differences in corneal epithelial thickness measurements with anterior segment… menstrual cycle [21], during pregnancy [27], and during hormone replacement therapy [28], suggesting a potential hormonal influence on corneal thickness, even while the exact role remains obscure [20,21]. Refractive status is another variable that could affect CET, but there are as yet no reports of a correlation between refraction and CET.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, cyclic variations in corneal topography and corneal thickness have been described. [1][2][3] These changes are probably driven by the direct interaction of sex hormones with sex hormone receptors located in the human cornea. 4,5 The Ocular Response Analyzer (ORA) (Reichert, Inc.) can be used to assess in vivo corneal biomechanical properties, which are presented by 2 parametersdcorneal hysteresis (CH) and the corneal resistance factor (CRF).…”
Section: Discussionmentioning
confidence: 99%
“…Kanellopoulos et al 4 and Wu et al 18 agreed with our findings; however, their studies show slightly smaller differences in the central epithelium with 1.52 lm and 1.34 lm, respectively. Research has shown the influence of gonadal hormones on ocular development 21,22 ; perhaps this can explain the difference.…”
Section: Sex and Axial Lengthmentioning
confidence: 99%